An integrative study to identify novel scaffolds for sphingosine kinase 1 inhibitors - Vettorazzi, Marcela (Eur J Med Chem, 2017)
Sphingosine kinase 1 (SphK1), the enzyme that produces the bioactive sphingolipid metabolite, sphin-gosine-1-phosphate, is a promising new molecular target for therapeutic intervention in cancer and inflammatory diseases. In view of its importance, the main objective of this work was to find new and more potent inhibitors for this enzyme possessing different structural scaffolds than those of the known inhibitors. Our theoretical and experimental study has allowed us to identify two new structural scaffolds (three new compounds), which could be used as starting structures for the design and then the development of new inhibitors of SphK1. Our study was carried out in different steps: virtual screening, synthesis, bioassays and molecular modelling. From our results, we propose a new dihydrobenzo[b] pyrimido[5,4-f]azepine and two alkyl{3-/4-[1-hydroxy-2-(4-arylpiperazin-1-yl)ethyl]phenyl}carbamates as initial structures for the development of new inhibitors. In addition, our molecular modelling study using QTAIM calculations, allowed us to describe in detail the molecular interactions that stabilize the different Ligand-Receptor complexes. Such analyses indicate that the cationic head of the different compounds must be refined in order to obtain an increase in the binding affinity of these ligands.